Flow-speed-controlled quality optimisation for one-shot-hybrid RTM parts - Patrick Hergan (Taylor & Francis Group, 2020)
This work describes a model-based methodology to improve the bonding quality between the metal and composite constituents of one-shot-hybrid resin transfer moulding (OSH-RTM) parts. In order to reduce void induced defects in the interface an ideal flow front velocity needs to be achieved. This ideal flow front velocity is characterised by capillary rise experiments at the used carbon fibre textile. The flow front velocity during mould filling is controlled by the use of pressure sensors and Darcy’s law. Therefore, viscosity characterisation of the resin system and permeability measurements of the preform were carried out. The interface of the produced OSH-RTM roof bar for a car is tested on a component test rig imitating the load of a side impact at a car. A t-test was carried out to prove that the flow-speed-controlled injection strategy is advantageous compared to a constant mass flow injection by means of a higher maximum load transferable by the interface of the hybrid part.